Pengukuran Pertumbuhan Volume Data Pada Sistem Informasi Pondok Pesantren - Yaqin, Muhammad Ainul; Ulhaq, Ahmad Ahya; Pratama, Kevin Syafri; Julkarnain, Muhammad (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2020)
Islamic boarding school information system is a system that can launch a variety of boarding school management processes with available features. The boarding school system also facilitates all aspects involved in the estimation and management of the pesantren. Which aims to find out ways and get important information related to a boarding school. Growth related to the problem of growth measurement will change a volume of data to the growth of large changes in number and size. Regression is a statistical analysis method used to see the effect between two or more variables. These variables are connected with functional properties that are realized in a mathematical model. This paper explains in detail how to measure the growth of the volume of data available in Islamic boarding schools. Measurement of data volume growth in the Islamic boarding school information system consists of metric complexity, number of transactions and the size of the data. The three components are then processed through multiple linear regression and will then produce a picture in the form of modeling that can later show predictions of data volume growth.